PRC2-dependent regulation of ganglioside expression during dedifferentiation contributes to the proliferation and migration of vascular smooth muscle cells - Sasaki, Norihiko; Hirano, Kazumi; Shichi, Yuuki; Itakura, Yoko; Ishiwata, Toshiyuki; Toyoda, Masashi (Frontiers in Cell and Developmental Biology, 2022)
Phenotypic switching between contractile (differentiated state) and proliferative (dedifferentiated state) vascular smooth muscle cells (VSMCs) is a hallmark of vascular remodeling that contributes to atherosclerotic diseases. Gangliosides, a group of glycosphingolipids, have been detected in atherosclerotic lesions and are suspected to contribute to the disease process. However, the underlying mechanism, specifically with respect to their role in VSMC phenotype switching, is not clear. In this study, we sought to reveal the endogenous expression of gangliosides and their functional significance in VSMCs during atherosclerosis. We found that switching from the contractile to proliferative phenotype was accompanied by upregulation of a- and b-series gangliosides, which in turn, were regulated by polycomb repressor complex 2 (PRC2). Downregulation of ganglioside expression using an siRNA targeting ST3GAL5, which is required for the synthesis of a- and b-series gangliosides, attenuated the proliferation and migration of dedifferentiated VSMCs. Therefore, we concluded that the increased expression of a- and b-series gangliosides via PRC2 activity during dedifferentiation is involved in the proliferation and migration of VSMCs. Gangliosides may be an effective target in VSMCs for atherosclerosis prevention and treatment.